Ultraviolet curing adhesive for reticular optical fiber ribbon and preparation method of ultraviolet curing adhesive
By using ultraviolet curing adhesives in the production of mesh fiber tape, the problems of insufficient adhesive bonding strength and slow curing speed are solved, and efficient and environmentally friendly mesh fiber tape production is achieved, improving the performance and production efficiency of the fiber tape.
Patent Information
- Application Number
- CN202411129359.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-16
- Publication Date
- 2024-12-17
AI Technical Summary
In the production process of existing mesh fiber tape, the adhesive bonding strength is insufficient, the curing speed is slow, and the peeling property is poor, resulting in poor performance of the fiber tape during winding and use, and cannot meet the needs of large-scale rapid production.
A UV curing adhesive has been developed, including carboxythiol tertiary carbonate polyurethane acrylate prepolymer, low viscosity prepolymer, tetrafunctional polyurethane modified silicone epoxy acrylate and other components, through specific synthesis routes and proportions , prepare adhesives with low viscosity, easy spraying and fast curing for the production of mesh fiber tapes.
It improves the bonding strength and torsion-resistant bending performance of the optical fiber tape, ensures that the fiber does not disperse the fiber, has good peeling performance, low curing shrinkage rate, is suitable for high-speed production, has no VOC emissions, is low odor, and meets environmental protection requirements.
Smart Images

Figure CN119144241A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical fibers and adhesives, and specifically discloses an ultraviolet curing adhesive for a mesh optical fiber ribbon and a preparation method thereof, which can realize UV / UV-LED light-induced rapid curing. Background Art
[0002] With the rapid development of the communications field, the domestic demand for large-core and ultra-large-core optical cables is increasing. In order to achieve high-density large-core optical cables, reelable mesh optical fiber ribbons have emerged. Compared with conventional optical fiber ribbons, mesh optical fiber ribbons have good flexibility and can be used after being reeled without affecting the optical properties of the optical fiber, which can realize the development of high-density optical cables with the same volume.
[0003] The existing production process of mesh optical fiber ribbons is to use a tiny droplet jetting device to spray adhesive onto the arranged colored optical fibers, and then cure them in a UV curing furnace. Since there is currently no adhesive specifically used for the production of mesh optical fiber ribbons, this production process has many shortcomings: (1) The bonding strength between optical fiber ribbons is insufficient, because the adhesive drops can only be dropped on the contact surface between two optical fibers, the bonding surface is small, and the ink layer on the surface of the colored optical fiber has a high degree of curing, which is both dense and relatively smooth. Ordinary glue is difficult to infiltrate, spread and penetrate the surface of the colored optical fiber. The insufficient bonding force of the adhesive leads to low bonding strength between optical fibers; (2) When there are many optical fiber core bundles, the droplets are diffusible. It is easy to diffuse to other optical fiber surfaces, making the shape of the mesh optical fiber ribbon affected and irregular; and due to the casting phenomenon of adhesive drops, it is easy to make the bonding point too long or too short. If the bonding point is too long, the winding performance of the optical fiber ribbon will deteriorate, and it may also increase the additional attenuation of the optical fiber ribbon. If the bonding point is too short, if the optical fiber shakes during the point processing, some bonding points will not be firmly bonded, resulting in the phenomenon of loose fibers in the production and subsequent processing; (3) Ordinary adhesives have a slow curing speed, resulting in incomplete curing, sticky surface, insufficient bonding strength, etc., affecting the product quality and production speed of the mesh optical fiber ribbon. The production efficiency is very low and cannot meet the needs of large-scale continuous and rapid production. (4) The adhesive bonding force is too strong, which makes it impossible to quickly, cleanly and completely separate a single optical fiber during subsequent use and installation, and even completely damages the optical fiber due to poor stripping properties.
[0004] Based on the above technical problems, there is an urgent need for a special adhesive for mesh optical fiber ribbons that has low viscosity, is easy to dispense or spray, quickly solidifies and bonds, effectively improves the bonding strength of the bonding points without causing additional attenuation to the optical fiber, and has good peelability to quickly separate a single optical fiber during construction. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a UV-curing adhesive and a preparation method thereof and an application in a mesh optical fiber ribbon; the adhesive has no VOC emissions, low odor, low viscosity and is easy to spray and dispense, has good adhesion to colored optical fibers when used in the mesh optical fiber ribbon, can effectively improve the bonding strength of the bonding points without causing additional attenuation to the optical fibers, and the prepared mesh optical fiber ribbon has good torsional and bending resistance, no fiber loosening, good peeling performance and low additional attenuation.
[0006] The technical scheme of the present invention is to provide a UV-curable adhesive, comprising the following raw materials in percentage by weight: 40-62% of carboxyl-mercapto-tertiary carbonate polyurethane acrylate prepolymer, 20-42% of low-viscosity prepolymer, 0.5-5% of tetrafunctional polyurethane modified silicone epoxy acrylate, 10-30% of high-adhesion acrylate monomer, 5-10% of acrylamide active monomer, 1%-5% of UV-curable cellulose ester, 1-4% of photoinitiator, 0.01-1% of leveling agent, 0.01-1% of photocurable degassing agent, and 0.01-0.5% of polymerization inhibitor, and the sum of the components meets 100%; The structure of the carboxyl-mercapto-tertiary carbonate polyurethane acrylate prepolymer is shown in Formula 1 below;
[0007] Formula 1.
[0008] Furthermore, the preparation route of the prepolymer described in Formula 1 is as follows: ; It includes the following steps: S1, using ethyl isocyanate acrylate and dimethylolbutyric acid as raw materials, adding a catalyst and an inhibitor, and heating the reaction to prepare an intermediate A; S2, using β-mercaptoethylamine and tert-butyl glycidyl carbonate as raw materials, reacting under a protective atmosphere to prepare intermediate B; S3 is prepared by adding a catalyst and a polymerization inhibitor to the intermediate A, the intermediate B and isophorone diisocyanate and heating them for reaction.
[0009] Furthermore, the preparation of Formula 1 meets any one or more of the following conditions: The molar ratio of the isocyanate ethyl acrylate and dimethylol butyric acid in S1 is 1:1; the reaction temperature in S1 is 40-45°C and the reaction time is 4-6 hours; The feeding amount of β-mercaptoethylamine and tert-butyl glycidyl carbonate in S2 is 1:1 in molar ratio; β-mercaptoethylamine in S2 is first dissolved in anhydrous ethanol, the reaction temperature is controlled at 8-12° C., and the reaction time is 5-7 hours; The molar ratio of isophorone diisocyanate, intermediate A and intermediate B in S3 is 1:1:1; the reaction temperature in S3 is 70-75° C., and the reaction time is 4-6 hours; The catalyst in S1 and S3 is dibutyltin dilaurate; the inhibitor in S1 and S3 is p-hydroxyanisole; The amounts of catalyst and inhibitor used in S1 and S3 are 0.1% to 0.5% of the total feed mass in the corresponding steps, respectively.
[0010] Furthermore, the viscosity of the low-viscosity prepolymer is less than 500 cps at 25° C.; the low-viscosity prepolymer includes but is not limited to a mixture of one or more of UV1847, UV7696, UV7697, and UV7424 produced by Zhongshan Qianyou Chemical Materials Co., Ltd. in any proportion.
[0011] Furthermore, the epoxy acrylate is a tetrafunctional polyurethane-modified silicone epoxy acrylate, and its synthesis route is as follows: ; The preparation process comprises the following steps: (1) After heating the terminal hydrogen-containing silicone oil, allyl glycidyl ether and a catalyst are added to react to obtain an intermediate C; (2) After heating the intermediate C, acrylic acid, a catalyst and an inhibitor are added to react to obtain the intermediate D; (3) Add a catalyst and an inhibitor to ethyl isocyanate acrylate and intermediate D, and heat to react to obtain the product.
[0012] Furthermore, the tetrafunctional polyurethane modified silicone epoxy acrylate meets any one or more of the following conditions during preparation: (1) The molar ratio of the feed amount of the middle-terminal hydrogen-containing silicone oil and allyl glycidyl ether is 1:2; the end-group hydrogen-containing silicone oil is preheated and then allyl glycidyl ether is added dropwise; the reaction temperature is 130-140°C and the reaction time is 3-4 hours; the catalyst is a platinum catalyst; the hydrogen content of the end-group hydrogen-containing silicone oil is 0.5-1.2%wt; (2) The molar ratio of the intermediate C to the acrylic acid is 1:2; acrylic acid is added dropwise after the intermediate C is preheated; the reaction temperature is 103-106°C, and the reaction time is 3-4 hours; the catalyst is an ammonium salt catalyst, and the inhibitor is p-hydroxyanisole; (3) The molar ratio of the amount of ethyl isocyanate acrylate to the intermediate D is 2:1; the reaction temperature is 50-55°C and the reaction time is 4-6 hours; the catalyst is dibutyltin dilaurate and the inhibitor is p-hydroxyanisole; In steps (1) to (3), the amount of catalyst and inhibitor used is 0.01% to 0.5% of the total feed mass of the corresponding step.
[0013] Furthermore, the high adhesion acrylate monomer includes but is not limited to a mixture of one or more of isobornyl acrylate, isobornyl methacrylate, cyclotrimethylolpropane formal acrylate, tetrahydrofurfuryl acrylate, 3,3,5-trimethylcyclohexyl acrylate, dicyclopentenyl ethoxylated acrylate, and 2-[[(butylamino)carbonyl]oxy]ethyl acrylate in any proportion.
[0014] Furthermore, the acrylamide reactive monomer includes but is not limited to a mixture of one or more of N,N-dimethylacrylamide and N,N-diethylacrylamide in any proportion.
[0015] Furthermore, the UV-curable cellulose ester includes but is not limited to a mixture of one or more of JS-113, JS-123, and JS-116 produced by Zhongshan Jieshida Fine Chemical Co., Ltd. in any proportion; the leveling agent includes but is not limited to a mixture of one or more of RAD 2700 and GLIDE 432 produced by Evonik Specialty Chemicals in any proportion; the photocurable degassing agent includes but is not limited to a mixture of one or more of TEG RAD 2500, TEG RAD 2600, and TEG RAD 2700 produced by Evonik Specialty Chemicals in any proportion.
[0016] Furthermore, the photoinitiator includes but is not limited to a mixture of one or more of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide (TMO), and 1-(9,9-dibutyl-9H-fluorene-2-yl)-2-methyl-2-morpholin-4-yl-propane-1-one (TR-NPI-20400) in any proportion; the inhibitor includes but is not limited to a mixture of one or more of hydroquinone, p-hydroxyanisole (MEHQ), and 3,5-di-tert-butyl-4-hydroxyphenylpropanoate (1135) in any proportion.
[0017] The present invention also relates to a method for preparing the ultraviolet curing adhesive, which comprises mixing the components in claim 1 in proportion, heating to 50-55° C., stirring for 1-2 hours in a dark environment, filtering and degassing after the stirring is completed, and obtaining the ultraviolet curing adhesive.
[0018] The invention also relates to the use of the ultraviolet curing adhesive as an adhesive for mesh optical fiber ribbons.
[0019] When it is specifically applied to the preparation of a mesh optical fiber ribbon, the colored optical fibers are arranged according to the designed structure, and the ultraviolet curing adhesive is sprayed on the gap between two adjacent colored optical fibers at a set position through a spray dispensing device, and then cured with a UV or UV-LED curing device to obtain a mesh optical fiber ribbon.
[0020] The present invention has the following beneficial effects: The UV-curing adhesive provided by the present invention has a viscosity (25°C) of 10-700 mPa.s, an elongation at break (25°C)>90%, an elastic modulus (25°C) of 20-500 MPa, a tensile strength (25°C) of 5-50 MPa, and a curing shrinkage of <3%; further preferably, the viscosity (25°C) is 100-500 mPa.s, the elongation at break (25°C)>100%, the elastic modulus (25°C) is 50-200 MPa, the tensile strength (25°C) is 10-30 MPa, and the curing shrinkage is ≤2%.
[0021] The UV-curable adhesive of the present invention has low viscosity and is easy to spray and dispense. In addition, the droplets are continuous during the spraying process without dripping or pausing. When used for a mesh optical fiber ribbon, the adhesive is sprayed on the surface of the colored optical fiber and diffuses and flows slowly, and can be cured and shaped in time. In addition, the adhesive has a fast curing speed and high production efficiency, and can meet the high-speed production requirements of more than 600 m / min.
[0022] The UV-curing adhesive provided by the present invention has excellent adhesion to colored optical fibers when used in mesh optical fiber ribbons, effectively improves the bonding strength of bonding points, and significantly improves the torsion resistance and bending resistance of optical fiber ribbons, thereby ensuring that the mesh optical fiber ribbons do not loosen or break fibers during the construction process, and have good reliability. The adhesive has low curing shrinkage stress and will not cause additional attenuation to the optical fibers. In addition, the adhesive has good peeling performance, and can quickly and completely separate a single optical fiber during construction without damaging the optical fiber.
[0023] The UV curing adhesive provided by the present invention has no VOC emission, low odor, complies with the latest EU REACH regulations, does not cause harm to the health of production personnel, and is very safe and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of the mesh optical fiber ribbon. DETAILED DESCRIPTION
[0025] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0026] The structure of the carboxyl-mercapto-containing tertiary carbonate polyurethane acrylate prepolymer of the present invention is as follows: .
[0027] The tertiary carbon group in the molecular structure of the prepolymer has a large steric hindrance, which can not only protect the ester bond of the tertiary carbonate from being decomposed, but also provide steric hindrance to the adjacent easily decomposable groups in the polymer, making it difficult to decompose, significantly improving their chemical resistance and weather resistance. The large volume structure of the tertiary carbon group reduces the intermolecular forces within the polymer (molecular chain entanglement, etc.), thereby greatly reducing the viscosity of the polymer. In addition, the tertiary carbonate group is provided by tertiary carbonic acid glycidyl ester, which has the advantages of high boiling point and low odor, and is very suitable for the preparation of high solids, solvent-free, light-cured low-VOC coatings and adhesives.
[0028] The above-mentioned prepolymer molecular chain also carries carboxyl, thiol and acrylate active functional groups. The carboxyl group can form a certain number of hydrogen bonds with the polar groups on the surface of the colored optical fiber, which greatly promotes the adhesion of the adhesive to the colored optical fiber. The thiol group and the acrylate group can undergo highly selective click reactions under the catalysis of free radicals cleaved by the photoinitiator, and the photopolymerization reaction system can complete the curing process under the conditions of a small amount of photoinitiator or even no photoinitiator. The photoinitiator efficiency is greatly improved, the curing rate is fast, and the conversion rate is high, which is conducive to the preparation of fast-curing adhesives, thus ensuring that the special adhesives for mesh and tapes can be completely cured under high-speed production conditions (>600m / min). The traditional UV curing process generally has oxygen inhibition effect, which leads to poor surface drying and seriously affects the surface properties of the material. In the photopolymerization reaction system of mercapto and acrylate, the peroxyl free radicals produced can capture the hydrogen atoms on the mercapto group and produce active mercapto free radicals, which ensure the continuous polymerization reaction. Therefore, the oxygen inhibition effect of the photopolymerization process of mercapto and acrylate is not obvious, which better ensures the good surface drying and surface properties of the mesh and tape special adhesive. Because the molecular chain of the mercapto-acrylate photopolymerization reaction is gradually growing, the molecular weight and degree of polymerization gradually increase, which makes it easy to release the curing shrinkage stress, thereby greatly reducing the internal stress of the mesh and tape special adhesive, so that it can better bond the colored optical fiber tightly together, without problems such as falling off and loose fibers, and will not cause additional attenuation to the optical fiber due to shrinkage stress, affecting the final optical performance of the optical fiber. After the photopolymerization reaction of mercapto-acrylate, thioether bonds are generated in the structure. The rotation barrier of thioether bonds in the cross-linked network structure is low, so that the product has quite good toughness and adhesion, heat resistance, oxidation resistance and low water absorption. In addition, the thiol group in the prepolymer molecule is directly introduced into the polymer molecular chain structure by chemical synthesis, rather than directly using small molecular thiol compounds in the composition formula, thus avoiding the problem of strong odor of thiol when directly used.
[0029] The carboxyl mercapto tertiary carbonate polyurethane acrylate prepolymer adopts isocyanate reactive diluent (ethyl isocyanate acrylate) and hydroxyl to react in one step to prepare polyurethane acrylate, thereby obtaining a prepolymer with narrow molecular weight distribution and low viscosity, thereby reducing the amount of diluent monomer in the product formula of light-curing adhesive.
[0030] The carboxyl-containing mercapto tertiary carbonate polyurethane acrylate prepolymer can be prepared by the following preparation route: ; The present invention provides a specific preparation method of carboxyl mercapto tertiary carbonate polyurethane acrylate prepolymer, but its preparation is not limited to the process conditions. Its preparation specifically includes the following steps: (1) 1 mol of ethyl isocyanate acrylate AOI-VM and 1 mol of dimethylolbutyric acid, 0.5% by weight of catalyst dibutyltin dilaurate and 0.1% by weight of inhibitor p-hydroxyanisole were added, and then the temperature was raised to 40-45°C for constant temperature reaction for 5 hours to obtain intermediate A; (2) Dissolve 1 mol of β-mercaptoethylamine in anhydrous ethanol, pass nitrogen through the flask for 30 minutes, use an ice bath to control the system temperature at about 10°C, then uniformly add 1 mol of tert-butyl glycidyl carbonate to the anhydrous ethanol solution of β-mercaptoethylamine, and control the addition time within 2 hours. After the addition is completed, control the reaction temperature at about 10°C and react for 6 hours to obtain intermediate B; (3) Add 0.5% by weight of the catalyst dibutyltin dilaurate and 0.1% by weight of the inhibitor p-hydroxyanisole to 1 mol of isophorone diisocyanate, 1 mol of intermediate A and 1 mol of intermediate B, raise the temperature to 70-75°C and react for 5 hours to obtain a carboxyl-containing mercapto tertiary carbonate polyurethane acrylate prepolymer.
[0031] In an optional case, the present invention also relates to a tetrafunctional polyurethane modified silicone epoxy acrylate, the structure of which is as follows: .
[0032] The UV-curing adhesive also incorporates tetrafunctional polyurethane-modified silicone epoxy acrylate, whose main chain is a silicone molecular chain with two acrylate double-bond functional groups at both ends of the molecular chain. The Si-O bond energy (450 kJ / mol) in the silicone polymer is much greater than the C-C bond energy (345 kJ / mol) and the C-O bond energy (351 kJ / mol), and has the advantages of good thermal stability, oxidation resistance, and weather resistance. The introduction of silicone segments into epoxy acrylate can reduce the internal stress of the cured product, increase toughness and heat resistance, and increase the wetting and leveling properties of the adhesive while maintaining the advantages of fast curing rate, strong adhesion, and good corrosion resistance. The compatibility problem between the acrylate molecular chain and the silicone segment is effectively solved by polyurethane modification and controlling the length of the introduced silicone segment. The four acrylate double-bond functional groups ensure its fast curing speed. The resin synthesis adopts specially customized terminal hydrogen-containing silicone oil with extremely low viscosity, and uses isocyanate with special structure for polyurethane modification, which reduces the introduction of carbamate groups, thereby ensuring the lower viscosity of polyurethane-modified silicone epoxy acrylate, which can effectively assist in regulating the final viscosity of the special adhesive for optical fiber ribbons, and can improve the wetting and coating performance of the special adhesive for optical fiber ribbons through its advantages such as good wettability and good leveling.
[0033] It can be prepared by the following process route: ; Its specific preparation process: (1) Heat 1 mol of terminal hydrogen-containing silicone oil to 130°C, then uniformly add a mixture of 2 mol of allyl glycidyl ether and 0.5% of the total amount of the reactants as a chloroplatinic acid catalyst, and after the addition is complete, heat to 130-140°C and continue the reaction at a constant temperature for 3 hours to obtain intermediate C; (2) 1 mol of intermediate C is heated to 100-105°C, and then 2 mol of acrylic acid and a mixture of 0.3% of the total amount of reactants in the form of an ammonium salt catalyst and 0.5% of a polymerization inhibitor p-hydroxyanisole are uniformly added dropwise. After the addition is complete, the reaction temperature is controlled at 103-106°C and the reaction is carried out for 4 hours to obtain intermediate D; (3) Add 2 mol of ethyl isocyanate acrylate and 1 mol of intermediate D, 0.05% of the total amount of the reactants as the catalyst dibutyltin dilaurate and 0.5% of the total amount of the reactants as the inhibitor p-hydroxyanisole, raise the temperature to 50-55°C and react for 5 hours to obtain tetrafunctional polyurethane-modified silicone epoxy acrylate.
[0034] The following embodiments also involve low viscosity prepolymer, high adhesion acrylate monomer, acrylamide reactive monomer, UV curable cellulose ester, photoinitiator, leveling agent, photocurable degassing agent and polymerization inhibitor.
[0035] In the preferred case, the low viscosity prepolymer has low viscosity (viscosity less than 500cps at 25°C), low odor, fast curing, and good adhesion, ensuring that the prepared mesh and special adhesive has low viscosity and is easy to spray and dispense, and fast curing can meet the curing requirements of high-speed production (>600m / min), and has good bonding strength for colored optical fibers. The low viscosity prepolymer can be selected from one or more of UV1847, UV7696, UV7697, and UV7424 produced by Zhongshan Qianyou Chemical Materials Co., Ltd., in any proportion.
[0036] In the preferred case, the high adhesion acrylate monomer has extremely strong dilution, dissolution and swelling capabilities, can quickly infiltrate and penetrate the surface of the colored optical fiber, and has a low curing shrinkage rate. The molecule has a polar ring structure, which is conducive to improving the adhesion of the adhesive product to the surface of the colored optical fiber. It can be selected from one or more of isobornyl acrylate, isobornyl methacrylate, cyclotrimethylolpropane formal acrylate, tetrahydrofurfuryl acrylate, 3,3,5-trimethylcyclohexyl acrylate, dicyclopentenyl ethoxylated acrylate, and 2-[[(butylamino)carbonyl]oxy]ethyl acrylate in any proportion.
[0037] In a preferred case, the acrylamide reactive monomer is used as a UV curing reactive monomer, which has the advantages of low viscosity, good dilution performance, good compatibility with various oligomers and reactive monomers, high curing rate, etc., and can also enhance the adhesion of the adhesive product to the substrate. The acrylamide reactive monomer can be a mixture of one or more of N,N-dimethylacrylamide and N,N-diethylacrylamide in any proportion.
[0038] In the preferred case, the UV-curable cellulose ester is prepared by reacting a cellulose derivative with a hydroxyl group with an acrylate or maleic anhydride with an isocyanate group to introduce an unsaturated double bond. This type of resin has the characteristics of large molecular weight, low shrinkage, good thixotropy, and high film-forming properties. Its thixotropy can be used to slow down the casting phenomenon of the adhesive droplets, prevent the droplets from diffusing to other optical fiber surfaces, and affect the shape of the mesh optical fiber ribbon, making it irregular, or causing undesirable phenomena such as too long or too short bonding points, which affect the molding and use of the optical fiber ribbon. The UV-curable cellulose ester can be selected from one or more of JS-113, JS-123, and JS-116 produced by Zhongshan Jieshida Fine Chemical Co., Ltd., in any proportion.
[0039] In a preferred case, the leveling agent is a special leveling agent that can promote leveling and has strippability, providing the mesh optical fiber ribbon with a certain degree of strippability, so that the cured glue can be quickly and cleanly removed in subsequent use to separate a complete single optical fiber. A mixture of one or more of Evonik Specialty Chemicals' RAD 2700 and GLIDE 432 in any proportion can be selected.
[0040] In the preferred case, the photocuring degassing agent has the characteristics of accelerating degassing and breaking bubbles, which can quickly eliminate bubbles in the matrix resin and prevent the coating defects caused by bubbles during the rapid spray dispensing and curing process of the adhesive, thereby affecting the final tensile strength and other mechanical properties. Unlike other degassing agents, because it contains acrylate functional groups, it can participate in the radiation cross-linking curing of the matrix resin, avoiding the migration and release of small molecules in the system. The photocuring degassing agent can be selected from one or more of Evonik Specialty Chemicals' TEG RAD 2500, TEG RAD 2600, and TEG RAD 2700 in any proportion.
[0041] In the preferred case, the photoinitiator has the characteristics of high initiation activity, no reproductive toxicity, low odor, and low migration, has good solubility and excellent thermal stability, complies with the latest EU REACH regulations, and can be used in UV and UV-LED curing systems. The photoinitiator can be selected from 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), (2,4,6-trimethylbenzoyl) di(p-tolyl) phosphine oxide (TMO), 1-(9,9-dibutyl-9H-fluorene-2-yl)-2-methyl-2-morpholin-4-yl-propane-1-one (TR-NPI-20400) in any proportion.
[0042] In a preferred case, the inhibitor is used to improve the storage stability of the adhesive and reduce the risk of premature gelation and curing of the adhesive during the dispensing process due to excessive sensitivity to light, which may block the nozzle. Specifically, the inhibitor can be selected from one or a mixture of any proportion of hydroquinone, p-hydroxyanisole (MEHQ), 3,5-di-tert-butyl-4-hydroxyphenylpropionate (1135).
[0043] Example 1 A UV-curing adhesive comprises the following components by weight percentage: 54% of carboxyl-mercapto-containing tertiary carbonate polyurethane acrylate prepolymer, 21% of UV1847 produced by Zhongshan Qianyou Chemical Material Co., Ltd., 3% of tetrafunctional polyurethane-modified silicone epoxy acrylate, 10% of high-adhesion acrylate monomer, 6% of N,N-dimethylacrylamide, 2.4% of UV-curable cellulose ester, 3% of photoinitiator, 0.22% of leveling agent, 0.08% of photocurable degassing agent, and 0.3% of polymerization inhibitor p-hydroxyanisole, and the sum of the components satisfies 100%.
[0044] Among them, the high adhesion acrylate monomer, by weight percentage, contains: 65% of cyclotrimethylolpropane formal acrylate and 35% of 3,3,5-trimethylcyclohexyl acrylate; the UV curable cellulose ester, by weight percentage, contains: 30% of JS-123 produced by Zhongshan Jieshida Fine Chemical Co., Ltd. and 70% of JS-116 produced by Zhongshan Jieshida Fine Chemical Co., Ltd.; the photoinitiator, by weight percentage, contains: 10% of 1-(9,9-dibutyl-9H-fluorene-2-yl)-2-methyl-2-morpholin-4-yl-propane-1-one (TR-NPI-20400) and 90% of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L); the leveling agent, by weight percentage, contains: 50% of Evonik Specialty Chemicals RAD 2700, 50% of Evonik's specialty chemical GLIDE 432; the light-curing degassing agent comprises, by weight percentage, 35% of Evonik's specialty chemical TEG RAD 2600 and 65% of Evonik's specialty chemical TEG RAD2700.
[0045] The preparation method of the adhesive is as follows: according to the above ratio, carboxyl mercapto tertiary carbonate polyurethane acrylate prepolymer, low viscosity prepolymer, tetrafunctional polyurethane modified silicone epoxy acrylate, high adhesion acrylate monomer, acrylamide active monomer, UV curable cellulose ester, photoinitiator, leveling agent, photocurable degassing agent and polymerization inhibitor are mixed and heated to 50-55° C., stirred for 2 hours in the dark, filtered and degassed after stirring to obtain the adhesive.
[0046] The performance of the adhesive prepared in this example was tested, and the results are shown in Table 1.
[0047] Table 1 Technical indicators of Example 1
[0048] Example 2 A UV-curing adhesive comprises the following components in percentage by weight: 43% of carboxyl-mercapto-tertiary carbonate polyurethane acrylate prepolymer, 22% of low-viscosity prepolymer, 5% of tetrafunctional polyurethane-modified silicone epoxy acrylate, 15.5% of high-adhesion acrylate monomer, 7% of N,N-diethylacrylamide, 3.2% of UV-curable cellulose ester, 3.5% of photoinitiator, 0.28% of leveling agent, 0.12% of photocurable degassing agent, and 0.4% of polymerization inhibitor hydroquinone, and the sum of the components satisfies 100%.
[0049] The low viscosity prepolymer comprises, by weight percentage, 60% of UV7424 produced by Zhongshan Qianyou Chemical Material Co., Ltd. and 40% of UV1847 produced by Zhongshan Qianyou Chemical Material Co., Ltd.; the high adhesion acrylate monomer comprises, by weight percentage, 45% of tetrahydrofurfuryl acrylate and 55% of 2-[[(butylamino)carbonyl]oxy]ethyl acrylate; the UV curable cellulose ester comprises, by weight percentage, 50% of JS-1 produced by Zhongshan Jieshida Fine Chemical Co., Ltd. 13. 50% of JS-116 produced by Zhongshan Jieshida Fine Chemical Co., Ltd.; the photoinitiator, by weight percentage, comprises: 20% of 1-(9,9-dibutyl-9H-fluorene-2-yl)-2-methyl-2-morpholin-4-yl-propane-1-one (TR-NPI-20400), 80% of (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide (TMO); the leveling agent, by weight percentage, comprises: 30% of Evonik Specialty Chemicals RAD2700, 70% of Evonik Specialty Chemicals GLIDE 432; the photocuring degassing agent, by weight percentage, comprises: 50% of Evonik Specialty Chemicals TEG RAD 2500, and 50% of Evonik Specialty Chemicals TEG RAD 2700.
[0050] The preparation method is the same as that in Example 1. The properties of the prepared adhesive are tested, and the results are shown in Table 2.
[0051] Table 2 Technical indicators of Example 2
[0052] Example 3 A UV-curing adhesive comprises the following components in percentage by weight: 46% of carboxyl-mercapto-containing tertiary carbonate polyurethane acrylate prepolymer, 30% of low-viscosity prepolymer, 2% of tetrafunctional polyurethane-modified silicone epoxy acrylate, 10% of high-adhesion acrylate monomer, 5.8% of acrylamide reactive monomer, 3% of UV-curable cellulose ester, 2.6% of photoinitiator, 0.24% of leveling agent Evonik Special Chemicals RAD 2700, 0.06% of photocuring degassing agent, and 0.3% of polymerization inhibitor p-hydroxyanisole, and the sum of the components satisfies 100%.
[0053] The low viscosity prepolymer comprises 75% of UV7696 produced by Zhongshan Qianyou Chemical Material Co., Ltd. and 25% of UV7697 produced by Zhongshan Qianyou Chemical Material Co., Ltd. by weight percentage; the high adhesion acrylate monomer comprises 80% of cyclotrimethylolpropane formal acrylate and 20% of dicyclopentenyl ethoxylated acrylate by weight percentage; the acrylamide active monomer comprises 80% of N,N-dimethylacrylamide and 20% of N,N-diethylacrylamide by weight percentage; the UV curable cellulose ester comprises 35% by weight percentage. The JS-113 produced by Zhongshan Jieshida Fine Chemical Co., Ltd. and 65% of JS-123 produced by Zhongshan Jieshida Fine Chemical Co., Ltd.; the photoinitiator comprises the following components by weight percentage: 11% of 1-(9,9-dibutyl-9H-fluorene-2-yl)-2-methyl-2-morpholin-4-yl-propane-1-one (TR-NPI-20400), 49% of (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide (TMO), and 40% of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L); the photocuring degassing agent comprises the following components by weight percentage: 70% of Evonik Specialty Chemicals TEG RAD2500 and 30% of Evonik Specialty Chemicals TEG RAD 2600.
[0054] The preparation method is the same as that in Example 1. The properties of the prepared adhesive are tested, and the results are shown in Table 3.
[0055] Table 3 Technical indicators of Example 3
[0056] Example 4 A UV-curing adhesive comprises the following components in percentage by weight: 40% of carboxyl-mercapto-containing tertiary carbonate polyurethane acrylate prepolymer, 26% of low-viscosity prepolymer, 1% of tetrafunctional polyurethane-modified silicone epoxy acrylate, 18% of cyclotrimethylolpropane formal acrylate, 8% of acrylamide reactive monomer, 4% of UV-curable cellulose ester, 2.4% of photoinitiator, 0.2% of leveling agent Evonik Special Chemical RAD 2700, 0.1% of photocuring degassing agent Evonik Special Chemical TEG RAD 25000, and 0.3% of polymerization inhibitor, and the sum of the components satisfies 100%.
[0057] The low viscosity prepolymer, by weight percentage, comprises 55% of UV1847 produced by Zhongshan Qianyou Chemical Material Co., Ltd. and 45% of UV7697 produced by Zhongshan Qianyou Chemical Material Co., Ltd.; the acrylamide active monomer, by weight percentage, comprises 50% of N,N-dimethylacrylamide and 50% of N,N-diethylacrylamide; the UV curable cellulose ester, by weight percentage, comprises 10% of JS-113 produced by Zhongshan Jieshida Fine Chemical Co., Ltd. and 90% of JS-116 produced by Zhongshan Jieshida Fine Chemical Co., Ltd.; 40% (2,4,6-trimethylbenzoyl) di(p-tolyl) phosphine oxide (TMO), 60% 2,4,6-trimethylbenzoyl phenylphosphonic acid ethyl ester (TPO-L). The inhibitor is calculated by weight percentage and its component content is: 60% p-hydroxyanisole, 40% 3,5-di-tert-butyl-4-hydroxyphenylpropionate (1135).
[0058] The preparation method is the same as that in Example 1. The properties of the prepared adhesive are tested, and the results are shown in Table 4.
[0059] Table 4 Technical indicators of Example 4
[0060] The adhesive prepared in the above-mentioned Examples 1 to 4 is used to prepare a mesh optical fiber ribbon, such as Figure 1 As shown, the colored optical fibers are first arranged according to the designed structure, and the liquid adhesive is sprayed on the gap between two adjacent colored optical fibers according to the set position by the spray dispensing equipment, and the UV-LED curing equipment is used for rapid curing, thereby preparing the mesh optical fiber ribbon with low attenuation, good anti-torsion bending performance, and good stripping performance of the present invention. The production speed of the mesh optical fiber ribbon is 700m / min; the curing equipment is a UV-LED curing lamp.
[0061] The prepared mesh optical fiber ribbon was subjected to optical fiber attenuation test, torsion test and peeling test, respectively, as follows.
[0062] 1) Optical fiber attenuation test: The adhesives prepared in Examples 1-4 were used to produce mesh optical fiber ribbons, and the attenuation of the optical fiber before and after ribbonization was tested. The results are shown in Tables 5 and 6.
[0063] Table 5 Attenuation of different colored fibers at 1310nm before and after banding
[0064] Table 6 Attenuation of different colored fibers before and after banding at 1550nm
[0065] It can be seen from the data in Table 5 and Table 6 that the special adhesives prepared in Examples 1-4 have little effect on the attenuation of the optical fiber after being tape-formed, thus meeting the use requirements.
[0066] 2) The torsion test meets the requirements of industry standards, that is, the optical fiber is rotated 180° clockwise over a length of 30 cm, returns to the initial position, then rotates 180° counterclockwise, and then returns to the initial position to form a cycle. The number of torsion cycles should be no less than 20. The results show that there is no cracking at the optical fiber bonding point.
[0067] 3) The optical fiber is stripped during the stripping experiment. The bonding points of the optical fiber can be stripped off smoothly. The stripped optical fiber is not damaged after testing.
[0068] In summary, the special adhesive for the mesh optical fiber ribbon of the present invention has the advantages of low viscosity, easy spraying and dispensing, slow casting, easy curing and shaping, fast curing speed to meet the needs of high-speed production (production speed>600m / min), good adhesion to colored optical fiber, low curing shrinkage, small additional attenuation of optical fiber, long storage time, etc., and does not contain harmful volatile substances, low odor, and meets the latest EU REACH regulations. The mesh optical fiber ribbon prepared by it has the advantages of low attenuation, good torsional bending resistance, and good peelability.
[0069] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A UV-curable adhesive for a mesh optical fiber ribbon, characterized in that: The invention comprises the following raw materials in percentage by weight: 40-62% of carboxyl-mercapto-tertiary carbonate polyurethane acrylate prepolymer, 20-42% of low viscosity prepolymer, 0.5-5% of tetrafunctional polyurethane modified silicone epoxy acrylate, 10-30% of high adhesion acrylate monomer, 5-10% of acrylamide active monomer, 1%-5% of UV-curable cellulose ester, 1-4% of photoinitiator, 0.01-1% of leveling agent, 0.01-1% of photocurable degassing agent, and 0.01-0.5% of polymerization inhibitor, and the sum of the components meets 100%; The structure of the carboxyl-mercapto-tertiary carbonate polyurethane acrylate prepolymer is shown in Formula 1 below; Formula 1.
2. The UV curing adhesive according to claim 1, characterized in that: The preparation route of the prepolymer described in Formula 1 is as follows: ; It includes the following steps: S1, using ethyl isocyanate acrylate and dimethylolbutyric acid as raw materials, adding a catalyst and an inhibitor, and heating the reaction to prepare an intermediate A; S2, using β-mercaptoethylamine and tert-butyl glycidyl carbonate as raw materials, reacting under a protective atmosphere to prepare intermediate B; S3 is prepared by adding a catalyst and a polymerization inhibitor to the intermediate A, the intermediate B and isophorone diisocyanate and heating them for reaction.
3. The UV curing adhesive according to claim 2, characterized in that: Formula 1 meets any one or more of the following conditions during preparation: The molar ratio of the isocyanate ethyl acrylate and dimethylol butyric acid in S1 is 1:1; the reaction temperature in S1 is 40-45°C and the reaction time is 4-6 hours; The feeding amount of β-mercaptoethylamine and tert-butyl glycidyl carbonate in S2 is 1:1 in molar ratio; β-mercaptoethylamine in S2 is first dissolved in anhydrous ethanol, the reaction temperature is controlled at 8-12° C., and the reaction time is 5-7 hours; The molar ratio of isophorone diisocyanate, intermediate A and intermediate B in S3 is 1:1:1; the reaction temperature in S3 is 70-75° C., and the reaction time is 4-6 hours; The catalyst in S1 and S3 is dibutyltin dilaurate; the inhibitor in S1 and S3 is p-hydroxyanisole; The amounts of catalyst and inhibitor used in S1 and S3 are 0.1% to 0.5% of the total feed mass in the corresponding steps, respectively.
4. The UV curing adhesive according to claim 1, characterized in that: The viscosity of the low-viscosity prepolymer is less than 500 cps at 25° C. The low-viscosity prepolymer includes but is not limited to a mixture of one or more of UV1847, UV7696, UV7697, and UV7424 produced by Zhongshan Qianyou Chemical Materials Co., Ltd. in any proportion.
5. The UV curing adhesive according to claim 1, characterized in that: The epoxy acrylate is a tetrafunctional polyurethane modified silicone epoxy acrylate, and its synthesis route is as follows: ; The preparation process comprises the following steps: (1) After heating the terminal hydrogen-containing silicone oil, allyl glycidyl ether and a catalyst are added to react to obtain intermediate C; (2) After heating the intermediate C, acrylic acid, a catalyst and an inhibitor are added to react to obtain the intermediate D; (3) Add a catalyst and an inhibitor to ethyl isocyanate acrylate and intermediate D, and heat to react to obtain the product.
6. The UV curing adhesive according to claim 5, characterized in that: The preparation of tetrafunctional polyurethane modified silicone epoxy acrylate meets any one or more of the following conditions: (1) The molar ratio of the feed amount of the middle-terminal hydrogen-containing silicone oil and allyl glycidyl ether is 1:2; the end-group hydrogen-containing silicone oil is preheated and then allyl glycidyl ether is added dropwise; the reaction temperature is 130-140°C and the reaction time is 3-4 hours; the catalyst is a platinum catalyst; the hydrogen content of the end-group hydrogen-containing silicone oil is 0.5-1.2%wt; (2) The molar ratio of the intermediate C to the acrylic acid is 1:2; acrylic acid is added dropwise after the intermediate C is preheated; the reaction temperature is 103-106°C, and the reaction time is 3-4 hours; the catalyst is an ammonium salt catalyst, and the inhibitor is p-hydroxyanisole; (3) The molar ratio of the amount of ethyl isocyanate acrylate to the intermediate D is 2:1; the reaction temperature is 50-55°C and the reaction time is 4-6 hours; the catalyst is dibutyltin dilaurate and the inhibitor is p-hydroxyanisole; In steps (1) to (3), the amount of catalyst and inhibitor used is 0.01% to 0.5% of the total feed mass of the corresponding step.
7. The UV curing adhesive according to claim 1, characterized in that: The high adhesion acrylate monomers include but are not limited to a mixture of one or more of isobornyl acrylate, isobornyl methacrylate, cyclotrimethylolpropane formal acrylate, tetrahydrofurfuryl acrylate, 3,3,5-trimethylcyclohexyl acrylate, dicyclopentenyl ethoxylated acrylate, and 2-[[(butylamino)carbonyl]oxy]ethyl acrylate in any proportion.
8. The UV curing adhesive according to claim 1, characterized in that: The acrylamide reactive monomers include, but are not limited to, a mixture of one or more of N,N-dimethylacrylamide and N,N-diethylacrylamide in any proportion.
9. The UV curing adhesive according to claim 1, characterized in that: The UV-curable cellulose ester includes but is not limited to a mixture of one or more of JS-113, JS-123, and JS-116 produced by Zhongshan Jieshida Fine Chemical Co., Ltd. in any proportion; the leveling agent includes but is not limited to a mixture of one or more of RAD 2700 and GLIDE 432 produced by Evonik Specialty Chemicals in any proportion; the photocurable degassing agent includes but is not limited to a mixture of one or more of TEG RAD2500, TEG RAD 2600, and TEG RAD 2700 produced by Evonik Specialty Chemicals in any proportion.
10. The UV curing adhesive according to claim 1, characterized in that: The photoinitiator includes but is not limited to a mixture of one or more of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester (TPO-L), (2,4,6-trimethylbenzoyl)di(p-tolyl)phosphine oxide (TMO), and 1-(9,9-dibutyl-9H-fluorene-2-yl)-2-methyl-2-morpholin-4-yl-propane-1-one (TR-NPI-20400) in any proportion; the inhibitor includes but is not limited to a mixture of one or more of hydroquinone, p-hydroxyanisole (MEHQ), and 3,5-di-tert-butyl-4-hydroxyphenylpropanoate (1135) in any proportion.
11. A method for preparing the UV-curable adhesive according to any one of claims 1 to 10, characterized in that: The components in claim 1 are mixed in proportion, heated to 50-55° C. and stirred in the dark for 1-2 hours, and filtered and degassed after the stirring is completed to obtain the product.
12. Use of the UV-curable adhesive according to any one of claims 1 to 10 or the UV-curable adhesive prepared according to claim 11 as an adhesive for a mesh optical fiber ribbon.
13. According to the use described in claim 12, when preparing a mesh optical fiber ribbon, the colored optical fibers are arranged according to the designed structure, and the ultraviolet curing adhesive is sprayed on the gap between two adjacent colored optical fibers at a set position by a spray dispensing device, and cured by UV or UV-LED curing equipment to obtain a mesh optical fiber ribbon.
Citation Information
Cited By
Ink composition, ink set, printed material, inkjet recording device, recording method, and method for manufacturing printed material
JP7915913B1
Ink composition, ink set, printed matter, inkjet recording device, recording method, and method for producing printed matter
WO2026211557A1
